Do transparency and anti-monopoly policies matter for financial development? Evidence from a panel ARDL-PMG approach - Shaohua Zhang; Farzan Yahya; Huy Pham; Muhammad Waqas (Journal of Applied Economics, 2021)
We examine the effect of macroeconomic stability, transparent government policies, and anti-monopoly policies on financial market development using extensive panel data of 113 countries over the period 2007 to 2017. By applying ARDL-PMG and controlling for GDP, trade openness, and market size, our findings reveal that macroeconomic stability fosters financial market development in both developing and developed countries. Effective transparency policies facilitate the link between macroeconomic stability and financial market development in the long-run. Furthermore, we find that anti-monopoly policies curb corruption and bureaucratic power to improve financial markets in the short-run. Still, a higher level of competition is more vulnerable to information asymmetry and adverse selection in the long-run.
Keywords: 330; Macroeconomic stability; anti-monopoly policies; transparency policies; financial market development; panel data analysis; PMG estimator